Unused cytotoxic drug reconstitude - Jaafar, Jamilah Rafaah; Mohamad, Noor Soriana; RamIi, Nur Aira Hazwani (2009)
Unused cytotoxic drug reconstituted mean the cytotoxic drug that have been prepared or made and delivered to the wards but not being used at a moment. This drug should be returned to the pharmacy as soon as possible for disposal in cytotoxic waste container. Whenever possible these drugs are reused for other patients. A research about unused cytotoxic drug was conducted at Hospital Sultanah Nur Zahirah , Kuala Terengganu(HSNZ).The main purpose of this study was to determine the factors or causes why unused cytotoxic drug happened, what are the effects and how to overcome that problem. All the data were collected from the oncology pharmacy which was included the cytotoxic drug reconstituted in year 2007 and 2008. The unused cytotoxic drug from the both years and the completed defaulter report that made by the oncology pharmacist were also collected. Furthermore, a survey among staffs and patients in HSNZ about that problem were conducted to get more information and to prove the data which was collected before. A lot of factors were identified and the most standing was patient's condition. That factor made up 46.8% of all factor reported. Results from surveying stated that year 2008 was the highest unused cytotoxic drug reported thus, it led the increasing cost of unused cytotoxic drug reconstituted. While the effect from this problem was the drug waste due to the respond majority staffs in HSNZ. In conclusion, patient's condition will explain a large number of unused cytotoxic drugs reconstituted. Therefore, the pharmacist needs to monitor the patient closely before the cytotoxic drug was given. Other staves also would have the responsibility to their patients and the careless can be reduced.